Catalytic performance of the tungstate-containing hydroxyapatite catalyst for the oxidation of benzyl alcohol at room temperature - Donskaya, Nadezhda O.; Goldberg, Margarita A.; Eseva, Ekaterina A.; Khayrutdinova, Dinara R.; Fomin, Alexander S.; Latypova, Sofya Sh.; Komlev, Vladimir S. (Elsevier, 2026)
Mesoporous nanopowders based on hydroxyapatite (HA) doped with tungstate groups up to 7.5 mol% were synthesized by precipitation. Low tungstate concentrations (from 1 to 2.5 mol%) yielded single-phase apatite, while higher concentrations (>= 5 mol%) led to CaWO4 co-precipitation. The obtained samples exhibited a substantial specific surface area (SSA) ranging from 74 to 88 m2/g and nanoscale particle size (10-25 nm). The 7.5 mol% tungstate-HA catalyst demonstrated high efficiency in the selective oxidative conversion of benzyl alcohol to benzaldehyde at room temperature. Optimal conditions were achieved, resulting in greater than 51 % substrate conversion, 100 % benzaldehyde selectivity, and a turnover frequency (TOF) of up to 180 h- 1. The high catalytic activity was attributed to active peroxo complexes, the large specific surface area, and the achieved porosity of up to 0.355 cm3/g. The findings of this study indicate that room temperature oxidative conversion with water as a coproduct is a promising green chemistry solution.
Keywords: Mesoporous hydroxyapatite; Calcium tungstate; Textural characteristics; Green oxidative process; Benzyl alcohol; Hydrogen peroxide